MORPHOMETRIC ANALYSIS OF SEAGRASSES SPECIES IN NEGROS ORIENTAL - Billy Th Wagey (JURNAL ILMIAH SAINS, 2013)
MORPHOMETRIC ANALYSIS OF SEAGRASSES SPECIES IN NEGROS ORIENTAL ABSTRAK Studi variasi morfometrik dari 5 spesies lamun di Negros Oriental Philippines dilaksanakan pada bulan Januari sampai Maret 2011. Pengukuran variable morfologi yang diambil adalah: panjang akar,  tinggi tegakkan lamun, panjang daun terpanjang  dalam cm.  Hasil studi menunjukkan: 1) Species Lamun yang diperoleh dari daerah Bais memiliki ukuran terkecil sedangkan lamun yang berasal dari Banilad yang tertinggi; 2) Diantara semua spesies yang teramati, Cymodocea rotundata tidak menunjukkan variasi morfometrik Kata Kunci: morfometrik, akar, daun terpanjang   ANALISIS MORFOMETRIK SPESIES LAMUN DI NEGROS ORIENTAL ABSTRACT A study of morphometric variations of five seagrass species in Negros Oriental, the Philippines was conducted from January to March 20011. Measurements of the following morphological variables were taken: length of rhizomes, length of upright shoot, length of longest leaf (cm). The study showed that: 1) Seagrass species from Bais had the lowest size range in morphometric measurements, whereas those from Banilad had the highest; 2) Among all the species observed, Cymodocea serrulata did not show morphometric variations. Keywords: morphometric, rhizome, longest leaf